Evaluating children's interactive products principles and practices for interaction designers - Markopoulos, P. (Panos) (Amsterdam ; Boston : Morgan Kaufmann, 2008)
Interactive products designed for childrenwhether toys, games, educational products, or websitesare increasingly embedded in childrens lives and school experiences. Making these products safe, effective, and entertaining requires new methodologies for carrying out sound and unbiased evaluations for these users with unique requirements, environments, and ethical considerations. This book directly addresses this need by thoroughly covering the evaluation of all types of interactive technology for children. Based on the authors' workshops, conference courses, and own design experience and research, this highly practical book reads like a handbook, while being thoroughly grounded in the latest research. Throughout, the authors illustrate techniques and principles with numerous mini case studies and highlight practical information in tips and exercises and conclude with three in-depth case studies. Essential reading for usability experts, product developers, and researchers in the field. * Presents an essential background in child development and child psychology, particularly as they relate to technology. * Captures best practices for observing and surveying children, training evaluators, and capturing the child user experience using audio and visual technology. * Examines ethical and legal issues involved in working with children and offers guidelines for effective risk management.
Includes bibliographical references and index.
Keywords: New products -- Design and construction; Interactive multimedia -- Evaluation; Children's paraphernalia -- Evaluation; Child consumers; Electronic books